What will be the result of this algebraic expression:
if we place
What will be the result of this algebraic expression:
if we place
We have the given exercise, and it has two variables, X and Y.
In this case, we are given the values of these variables,
Therefore, what we need to do is substitute them in the relevant place in the exercise:
8(x-7)+4(6-2y)=
We know that x=0, so we will replace every X in the exercise with 0:
8(0-7)+4(6-2y)=
8(-7)+4(6-2y)=
-56+4(6-2y)=
We'll do the same thing with y, knowing that it equals -1
-56+4(6-2*(-1))=
-56+4(6-(-2)))=
-56+4(8)=
-56+32=
-24
And that's the solution!